Expert Answers
justaguide eNotes educator| Certified Educator

43 = 7 - 3x(-12) is an equation.

Solving 43 = 7 - 3x(-12) gives:

43 = 7 + 36x

=> x = 1

The solution of the equation is x = 1.

jess1999 | Student

43 = 7 - 3x(-12) 

First distribute the -3x

By distributing, you should get

43 = 7 + 36x now subtract 7 on both sides

By subtracting, you should get

36 = 36x divide both sides by 36

By dividing, you should get

X = 1 which is your answer

atyourservice | Student

`43 = 7 - 3x(-12)`

`43 = 7+36x`  combine like terms

`43-7=36x`

`36=36x`

`36/36 = (36x)/36`    1=x

tamtamtameena | Student

43=7-3x(-12)

43=7+36x 

43-7=36x

36=36x

x=36/36

x=1

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question